Case report: Varicella-zoster virus infection triggering progressive encephalomyelitis with rigidity and myoclonus - Yuan, Jing; Wang, Aihua; Hou, Yunfeng; Xu, Xuxu (Frontiers in Neurology, 2022)
Progressive encephalomyelitis with rigidity and myoclonus (PERM) is a rare neurological disease of unknown etiology, and most patients with PERM are positive for anti-glycine receptor (GlyR) antibody. In this case study, we report a clinical case of a varicella-zoster virus-infected patient who developed anti-GlyR antibody-positive PERM. He initially suffered from herpes zoster and gradually developed symptoms of impaired brainstem functions including hoarse voice and dysphagia, accompanied by paroxysmal sympathetic hyperactivity. The patient also suffered from severe spasms, which were easily triggered by external stimuli. Glycine receptor antibodies were then found to be positive in serum and cerebrospinal fluid, and the diagnosis of PERM was confirmed. Methylprednisolone and gamma globulin treatments were given, and spasms were improved after treatment. Unfortunately, the patient's family insisted on automatic discharge and the patient passed away several days later.